BUMDes DEVELOPMENT STRATEGY IN A COLLABORATIVE GOVERNANCE PERSPECTIV - Da Kunha, Kosmas; Said, Abdullah; Hidayati, Firda (Faculty of Administrative Science, Universitas Brawijaya, 2024)
Village-Owned Enterprises (BUMDes) are a new approach to efforts to improve the village economy. This business entity formed by the village government is said to be the most implicative and replicative business entity because it replicates the self-governing community empowerment model . In Magepanda District, for example, there are 5 BUMDes units with a total initial capital of IDR. 669,000,000, currently in a collapsed condition. Many BUMDes are no longer operating, due to mismanagement, capital difficulties and managerial limitations at the management level of the business entity itself.This research aims to implement a BUMDes development strategy with a Collaborative Governance perspective in a number of BUMDes in Magepanda District. A development strategy with this perspective requires cooperation between the government, private sector and the community in the management and development of BUMDes.This research ultimately resulted in the formulation of a BUMDes development strategy from a collaborative governance perspective which requires cooperation between government, community and private elements in the development of Village-Owned Enterprises by applying the aspects contained in the CGRs typology. . This also serves as a recommendation for village governments and regional governments to implement the strategy in the context of developing BUMDes in the future.